(untitled) - Stuart M Blumin (Cambridge, New York, 1989)
This book looks past old clichés to trace, in the experiences and social identities of urban middling folk, the emergence of a recognizable and self-aware "middle class" between the era of the American Revolution and the end of the nineteenth century
Keywords: middle classes - united states - history - 18th century,middle classes - united states - history - 19th century